2002
DOI: 10.1637/0005-2086(2002)046[0757:siiosc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Stomach Impaction in Ostriches (Struthio camelus): Blood Chemistry, Hematology, and Treatment

Abstract: This study involved 14 ostriches of both sexes between 3 and 24 mo of age. Some hematologic and biochemical parameters were studied in animals with stomach impaction. Clinical examination of the birds revealed anorexia, emaciation, decreased defecation, listlessness, separation from the flock, and recumbence. The total number of leukocytes (10.4 x 10(3) mm3), the concentrations of serum glucose (166 mg/dl), and total protein (2.4 g/dl) decreased; serum creatine phosphokinase (1240 U/L) and alkaline phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
0
11
2
Order By: Relevance
“…Values of copper concentration were lower in relation to reported results of copper concentration measurements in the blood of ostriches at the age of 1 to 3 months (Bezuidenhout et al, 1994;Yüksek et al, 2002) and in adults (Yüksek et al, 2002.;Agaoglu et al, 2003). Copper is essential for feather pigmentation, bone formation and egg production.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Values of copper concentration were lower in relation to reported results of copper concentration measurements in the blood of ostriches at the age of 1 to 3 months (Bezuidenhout et al, 1994;Yüksek et al, 2002) and in adults (Yüksek et al, 2002.;Agaoglu et al, 2003). Copper is essential for feather pigmentation, bone formation and egg production.…”
Section: Resultscontrasting
confidence: 58%
“…Erythrocyte parameters (erythrocyte count, haemoglobin concentration, haematocrit, MCV, MCH and MCHC) of one-day old ostriches in our research were lower in relation to values reported in the blood of younger groups (1 -20 months) and in adult birds(Levi et al, 1989;Palomeque et al, 1991;Hopkins, 1995;Brown and Jones, 1996;Romdhane et al, 2000;Yüksek et al, 2002;Agaoglu et al, 2003).…”
contrasting
confidence: 68%
“…Since the Salmonella spp. is a large set of important zoonotic pathogens, during the last several decades, many methods have been tried for detecting Salmonella in kinds of samples during the last several decades (Proux et al 2002; Shi et al 2015; Bell et al 2016; Wang and Salazar 2016). Immunological techniques have a great potential for the detection of Salmonella because of their rapidness, sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The objects of research were ostriches of different age groups. A clinical examination of black African ostriches (Struthio camelus Linnaeus, 1758), Australian common Emu (Dromaius novaehollandiae Latham, 1790) and rhea (Rhea americana Linnaeus, 1758) was carried out according to existing methods (Yüksek et al, 2002;Buergelt, 2020). Helminoproscopic studies of fecal samples from ostriches of different age groups were carried out using the method of direct smear and concentration (flotation and sedimentation) (Tomza-Marciniak et al, 2014;Byrnea et al, 2018;Ola-Fadunsin et al, 2019).…”
Section: Methodsmentioning
confidence: 99%